The Role of Fiction Writers in the Development of Kiswahili. Issue 3 (2nd October 2019) - Mohochi, Ernest Sangai
ABSTRACT: This paper analyses fiction writers' contribution to the development of Kiswahili language. The paper is anchored on the assumption that writers play a big role in the development of language. The contribution of fiction writers has not been widely investigated. This paper analyses the position that creative writers in Swahili literature have accorded this language in their works, and how this position contributes to the development of the language. Additionally, there is a discussion on how writers affect readers' appreciation of the importance of the Swahili language. This study was guided by social influence theory that holds that popular and distinguished people have a lot of influence that can shape others in society. Writers have this characteristic and so they can shape the outlook and views of their readers on the importance of the Swahili language. The data used in this paper was collected by reading the fictional works of three writers of Swahili literature who were purposively sampled: Shaaban Robert, Wallah bin Wallah, and Ken Walibora, together with questionnaires sent to 40 students and 8 lecturers at Rongo University. Similarly, these authors' works were purposively sampled. Findings of this study show that these writers have given Kiswahili a special position in society and have used admirable characters who love and defend the language, thus influencing the readers to also love Swahili.